THE CONCEPT OF REPRESENTATION OF GEOMETRIC SOLIDS IN BUILDING INFORMATION MODELING - Konopatskiy, Evgeniy; Bezsolnov, Maxim (International Journal for Computational Civil and Structural Engineering, 2025)
The problem of using the boundary model of geometric solids representation in BIM is formulated. A new concept of solid geometric modeling is presented, which allows to define geometric solids as a selected part of space, according to which geometric solids are represented by an organized set of points by analogy with other geometric objects. The mathematical apparatus “Point Calculus” is used for analytical description of geometric solids. Examples of modeling geometric solids in point calculus are given. The advantages of this approach are the possibility of representation of geometric information in BIM in compact vector form and realization of parallel calculations at the level of mathematical apparatus. The prospect of further research is the use of the proposed concept for the representation of various elements of building structures with the subsequent optimization of the representation of geometric objects in the IFC format. This will significantly reduce the volume required for the transfer of geometric information between the systems of information modeling and computer-aided design, increase their performance and radically solve the problem of interoperability of existing BIM software packages. Сформулирована проблема использования граничной модели представления геометрических тел в ТИМ. Представлена новая концепция твердотельного геометрического моделирования, которая позволяет определять геометрические тела в виде выделенной части пространства, в соответствии с которой геометрические тела по аналогии с другими геометрическими объектами представляются организованным множеством точек. Для аналитического описания геометрических тел используется математический аппарат «Точечное исчисление». Приведены примеры моделирования геометрических тел в точечном исчислении. Преимуществами такого подхода является возможность представления геометрической информации в ТИМ в компактной векторной форме и реализация параллельных вычислений на уровне математического аппарата. Перспективой дальнейших исследований является использование предложенной концепции для представления различных элементов строительных конструкций с последующей оптимизацией представления геометрических объектов в формате IFC. Это позволит в значительной мере сократить объём необходимый для передачи геометрической информации между системами информационного моделирования и автоматизированного проектирования, повысить их быстродействие и радикально решить проблему интероперабельности существующих ТИМ в строительной отрасли.